The Role of Acidity in the Synthesis of Novel Uranyl Selenate and Selenite Compounds and Their Structures - Gabriel L. Murphy; Philip Kegler; Eike M. Langer; Evgeny V. Alekseev (Crystals, 2021)
Herein, the novel uranyl selenate and selenite compounds Rb2[(UO2)2(SeO4)3], Rb2[(UO2)3(SeO3)2O2], Rb2[UO2(SeO4)2(H2O)]·2H2O, and (UO2)2(HSeO3)2(H2SeO3)2Se2O5 have been synthesized using either slow evaporation or hydrothermal methods under acidic conditions and their structures were refined using single crystal X-ray diffraction. Rb2[(UO2)2(SeO4)3] synthesized hydrothermally adopts a layered 2D tetragonal structure in space group P42/ncm with a = 9.8312(4) Å, c = 15.4924(9) Å, and V = 1497.38(15) Å, where it consists of UO7 polyhedra coordinated via SeO4 units to create units UO2(SeO4)58− moieties which interlink to create layers in which Rb+ cations reside in the interspace. Rb2[(UO2)3(SeO3)2O2] synthesized hydrothermally adopts a layered 2D triclinic structure in space group P<semantics><mover accent="true">1¯</mover></semantics> with a = 7.0116(6) Å, b = 7.0646(6) Å, c = 8.1793(7) Å, α = 103.318(7)°, β = 105.968(7)°, γ = 100.642(7)° and V = 365.48(6) Å3, where it consists of edge sharing UO7, UO8 and SeO3 polyhedra that form [(UO2)3(SeO3)2O2] layers in which Rb+ cations are found in the interlayer space. Rb2[UO2(SeO4)2(H2O)]·2H2O synthesized hydrothermally adopts a chain 1D orthorhombic structure in space group Pmn21 with a = 13.041(3) Å, b = 8.579(2) Å, c = 11.583(2) Å, and V = 1295.9(5) Å3, consisting of UO7 polyhedra that corner share with one H2O and four SeO42− ligands, creating infinite chains. (UO2)2(HSeO3)2(H2SeO3)2Se2O5 synthesized under slow evaporation conditions adopts a 0D orthorhombic structure in space group Cmc21 with a = 28.4752(12) Å, b = 6.3410(3) Å, c = 10.8575(6) Å, and V = 1960.45(16) Å3, consisting of discrete rings of [(UO2)2(HSeO3)2(H2SeO3)2Se2O5]2. (UO2)2(HSeO3)2(H2SeO3)2Se2O5 is apparently only the second example of a uranyl diselenite compound to be reported. A combination of single crystal X-ray diffraction and bond valance sums calculations are used to characterise all samples obtained in this investigation. The structures uncovered in this investigation are discussed together with the broader family of uranyl selenates and selenites, particularly in the context of the role acidity plays during synthesis in coercing specific structure, functional group, and topology formations.